Effects of freezing and microwaving conditions on the pH, total plate count, and acceptability of chicken-pork adobo - Cava, Fatima Ria I.
This study was conducted to determine the effects of frozen strorage period (days) and microwavinf conditions to pH, total plate count, and acceptability of chicken-pork adobo.